Denmark, Durkheim, and Decentralization: The Structures and Capabilities of Danish Working Lives - Byrne, John-Paul (Nordic Journal of Working Life Studies, 2018)
Over the last two decades, a range of reports and cross-sectional surveys of European workers have highlighted Denmark as scoring exceptionally, and consistently, well across several dimensions shaping working life, for example, job quality, work-life balance, discretion and learning, and job satisfaction. This is despite a trend of increasing psychosocial risks of work across Europe. Providing a retrospective interpretation of this exceptionalism, the paper draws on data from 40 expert interviews in Denmark to theoretically map the advantageous institutional components shaping working life in Denmark. Aligning the theories of Émile Durkheim with the capabilities framework, the analysis highlights the role of interdependent collective agreements, which link macro and microwork contexts and generate resources that augment the experience of balance and control within working life